A Rare Case of Pulmonary Artery Dissection Associated With Infective Endocarditis. Issue 19 (May 2016) - Shi, Xiaoqing; Wang, Xiaoqin; Wang, Chuan; Zhou, Kaiyu; Li, Yifei; Hua, Yimin
Abstract : Abstract: Pulmonary artery dissection (PAD) is a rare condition with high mortality and has not been reported in patient with infective endocarditis (IE). Here, we report the first case of such patient who experienced PDA and survived after surgical intervention. A 10-year-old female child was diagnosed as IE with a patent ductus arteriosis (PDA) and a vegetation on the left side of pulmonary artery trunk (10 × 5 mm 2 ). Following 3-week antibacterial treatment, the body temperature of patient returned to normal, and the size of vegetation reduced (7 × 3 mm 2 ). However, the patient had a sudden attack of sustained and crushing right chest pain, orthopnea with increasing respiratory rate (> 60/min), and acute high fever. Echocardiography revealed the detachment of vegetation on the first day and dissection of pulmonary artery on the next day. The patient received immediate surgical intervention. It was found that aneurysm had a size of 28 × 20 mm 2 and its orifice (the dissecting site) located on the opposite side of the PDA opening (right side of the pulmonary artery trunk). The dissected left wall of pulmonary artery trunk was reconstructed followed by the closure of PDA with suture. The patient recovered uneventfully. From this case, we learned that the surgical intervention should be considered at an early time for IE patients who have a vegetation in pulmonary artery and PDA. After the infection is under control, the earlier surgery may prevent severe complications.